Severe Dehydration Due to Low Intake in Patients with Oral Candidiasis in Malignancy: A Case Report - Theresia Monica Rahardjo; Brenli Orville Sumarlie; Erinetta Koeswandy Kho; Laudry Fanthera; Liyenka Belusi Tantra; Nathalia Gabriella (Medical Clinical Update, 2023)
Oral candidiasis is an infection in oral cavity caused by Candida albicans. This disease is frequently caused by immunological suppression, which can be local or systemic, caused by immunosuppression due to extremes of age (newborns and the elderly), diseases that impair immunity, such as in infection of human immunodeficiency virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS), long-term systemic steroid use, and long-term systemic antibiotic use. Oral candidiasis could lead to low-intake condition due to swallowing difficulties. This case report aimed to present a patient with severe dehydration due to oral candidiasis that needs to be hospitalized.